Analysis of Online Learning Media and Its Usage in English Learning in SMA Negeri in Tarakan - winarno, winarno; Fitriawati, Fitriawati (Linguistics and ELT Journal, 2023)
The objectives of the study were to analyze online learning media used by English teachers at SMA Negeri in Tarakan and find out the important factors that influence the successful use of online learning media by English teachers at SMA Negeri in Tarakan North Kalimantan. The study was descriptive qualitative. The subjects were the teachers of English at SMA Negeri in Tarakan. To collect the data used observations, interviews and documentation and to analyze the data used the stages of Miles and Huberman. The stages are data collection, data reduction, data display, and conclusions: drawing and verifying. The results of the study showed that 1) the online learning media platforms used by English teachers at SMA Negeri in Tarakan were quite varied. The online learning media platforms include google classroom (84.6%), google meet (76.9%), Whats-App group (76.9), zoom meeting application (61.5%), Microsoft teams (15.4), telegram (46.2), rumah belajar (7.7%), you-tube (61.5%), madrasah e-learning (7.7%), google form (7.7%), quiziz (7.7%), online test provider websites (7.7%) and eduku (7.7%). Most of the English teachers at SMA Negeri in Tarakan used the Google Classroom online learning media platform, 2) The success of online learning on English at SMA Negeri in Tarakan was influenced by teacher factors, technological factors and design and content factors.